2017
DOI: 10.1016/j.amjmed.2016.11.038
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prolonged Glucosamine Usage on HbA1c Levels and New-Onset Diabetes Mellitus in Overweight and Obese Middle-Aged Women

Abstract: There was no effect of glucosamine sulfate on mean HbA1c level nor on obtaining a high HbA1c level or new-onset diabetes mellitus over 6.5 years, especially in participants with a normal HbA1c level at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…61 In this sense, however, a large RCT comprising 407 overweight and obese women, followed up for 2.5 years, reported that there was no significant effect of a 2.5-year GS intervention on mean glycosylated haemoglobin level. 62 Present data, although limited by the narrative nature of the review, confirmed that GS is safe from a metabolic point of view, being in agreement with a large longitudinal study using the UK Biobank showing that the use of GS in OA is associated with a lower incidence of diabetes, over 8 years of follow up. 63 In the same database, it is reported that GS can lead to a reduction in cardiovascular disease 64 and all-cause and specific-cause mortality.…”
Section: Authorsupporting
confidence: 85%
“…61 In this sense, however, a large RCT comprising 407 overweight and obese women, followed up for 2.5 years, reported that there was no significant effect of a 2.5-year GS intervention on mean glycosylated haemoglobin level. 62 Present data, although limited by the narrative nature of the review, confirmed that GS is safe from a metabolic point of view, being in agreement with a large longitudinal study using the UK Biobank showing that the use of GS in OA is associated with a lower incidence of diabetes, over 8 years of follow up. 63 In the same database, it is reported that GS can lead to a reduction in cardiovascular disease 64 and all-cause and specific-cause mortality.…”
Section: Authorsupporting
confidence: 85%
“…In addition, a meta-analysis on the effects of glucosamine on glucose metabolism found that glucosamine, at the usual oral doses used in knee OA patients, is well-tolerated by normal, diabetic, or pre-diabetic patients [56]. In the PROOF trial, a non-significant increase in glycated hemoglobin levels was found in overweight women who received pCGS during the follow-up period [57,58]. Thus, the SEAWG recommends to advise caution at the start of treatment with glucosamine in diabetic patients [59].…”
Section: Sysadoasmentioning
confidence: 99%
“…20,24 Seven studies recruited only healthy subjects. 11,[15][16][17]21,22,25 Only two studies recruited osteoarthritic patients. 19,26 One study randomised the subjects according to obesity status i.e.…”
Section: Sample Size and Characteristicsmentioning
confidence: 99%
“…17 Five of the studies merely reported the mean BMI 10,15,17,18,21 from which three of the studies reflected that the subjects were mostly obese as the mean BMI was more than 30. 18,22,23 Glucosamine Dosing Six of the studies followed the recommendation of dosing in the CPG Management of Osteoarthritis 2 nd Ed 2013 11,[18][19][20]22,26 while one prospective study reported affirmative use of glucosamine but no specific information provided on the dosing. 21 Three of the studies used the recommended dose but at a shorter duration of between 14 to 42 days.…”
Section: Sample Size and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation